2014
DOI: 10.1007/s10858-014-9839-x
|View full text |Cite
|
Sign up to set email alerts
|

A reduced dimensionality NMR pulse sequence and an efficient protocol for unambiguous assignment in intrinsically disordered proteins

Abstract: Resonance assignment in intrinsically disordered proteins poses a great challenge because of poor chemical shift dispersion in most of the nuclei that are commonly monitored. Reduced dimensionality (RD) experiments where more than one nuclei are co-evolved simultaneously along one of the time axes of a multi-dimensional NMR experiment help to resolve this problem partially, and one can conceive of different combinations of nuclei for co-evolution depending upon the magnetization transfer pathways and the desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Chemical shi assignments were obtained by transfer from BMRB (accession number 16300) and other previous reports. 45,46 Chemical shi perturbations (CSP) were calculated Native-polyacrylamide gel electrophoresis (native-PAGE)…”
Section: Nuclear Magnetic Resonance (Nmr) Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical shi assignments were obtained by transfer from BMRB (accession number 16300) and other previous reports. 45,46 Chemical shi perturbations (CSP) were calculated Native-polyacrylamide gel electrophoresis (native-PAGE)…”
Section: Nuclear Magnetic Resonance (Nmr) Spectroscopymentioning
confidence: 99%
“…(A) 1 H-15 N HSQC spectrum of aSyn in the presence (blue) and absence (red) of 0.75 mg ml À1 Triphala. The peaks were assigned by transfer of assignments from BMRB (accession number 16300) and other previous reports 45,46. (B) Chemical shift perturbation (CSP) for 150 mM aSyn observed in 1 H-15 N HSQC spectra in the presence of 0.75 mg ml À1 Triphala relative to free aSyn.…”
mentioning
confidence: 99%
“…Multidimensional experiments generating sequential amide correlations, such as (H)N(CA)NH, (H)N(COCA)NH and HN(CA)CONH, have been extensively applied to IDPs 4d. h, j, l Considering that [ 1 H, 15 N]‐resolved triple‐resonance experiments may not always lead to satisfactory results in the study of disordered systems, either due to poor dispersion of cross‐peaks in the 15 N– 1 H correlation spectra or due to fast exchange of the solvent‐exposed labile protons with water protons, a variety of alternative strategies involving 1 H α and 13 C direct detection have been reported for the study of IDPs 5. From these studies it is apparent that dispersion of inter‐residue cross‐correlation peaks observed in spectra such as 15 N– 13 C′ and 13 C′– 1 H N is typically better than the intra‐residue cross peaks′ dispersion in conventional [ 1 H, 15 N]‐correlation spectra of disordered proteins 4i.…”
mentioning
confidence: 99%
“…Frequency switching in the 13 Ca nd 1 Hc hannels was carried out, where needed, whent he relevant magnetisation was along the z-axis. The uniformly ( 13 C, 15 N) labelled sample of a-synuclein (pH 6.2, 1.5 mm), an IDP that has been extensively studied via solution-state NMR, [1,2,22,42,56,57] was prepareda sp er established procedures. [58] The non-uniformly sampled multidimensional data sets were collectede mploying random sampling in the indirect dimensions and processed with the multidimensional decomposition processing protocol [59] availablei n the Bruker To pspin version 3.2 software.…”
Section: Dedicatedtoprof Drp Eter Schuster( Vienna) On the Occasionmentioning
confidence: 99%